Determining the impacts of pedestrian facility improvements on mode choice of car users a case study of the Ortigas Center - Brillon, Edgardo A. (School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
Being the focal point of a city, Central Business Districts (CBDs) suffer from traffic congestion. Several solutions that are usually implemented to mitigate the impacts of congestion are road construction and road widening. However, one possible solution that is overlooked is the promotion of non-motorized transportation like walking. This research study aims to determine how improvements on pedestrian facilities would affect the mode choice of car users in Ortigas Center. Finding specific pedestrian facilities that have a likelihood of influencing the mode choice of existing car users would be crucial in planning to implement improvements in pedestrian facilities, as well as reduce car trips within the CBD. A revealed preference and stated preference survey was conducted to determine the trip characteristics and preferences of the car users that would entice them to use public transport or walking. The target sample size is 400 respondents and was divided into 4 zones within Ortigas Center. The results of the survey were used to come up with a list predictors for the binary logistic regression models.The resulting binary logistic regression model for trips going in and out of Ortigas Center indicates that age, educational attainment, trip frequency, trip purpose, and the presence of sidewalk railings are significant predictors of mode shift. Increasing age and frequent trips were associated to an increased likelihood of mode shift while being a college graduate and shopping trips were associated to decreased likelihood of mode shift. The presence of sidewalk railings increases the likelihood of mode shift 2.55 times as compared to none. for the sub-analysis for those located near office building with trips going in and out of Ortigas Center, educational attainment, trip frequency, trip purpose, presence of wide sidewalks and walkways, and the presence of connection to public transport terminals/stops are significant predictors of mode shift. More frequent trips were associated to an increased likelihood of mode shift while being a college graduate and shopping trips were associated to a decreased likelihood of mode shift. The presence of wide sidewalks and walkways increases the likelihood of mode shift to 4.66 times as compared to none while the presence of connection to public transport terminals/stops increases the likelihood of mode shift to 2.68 times as compared to none. The resulting binary logistic regression model for trips within Ortigas Center indicates that educational attainment and the presence of covered sidewalks and walkways are significant predictors of mode shift. Being a college graduate was associated to a decreased likelihood of mode shift. The presence of covered sidewalks and walkways increases the likelihood of mode shift to 4.17 times as compared to none. For the sub-analysis for those located near office buildings with trips around Ortigas Center, educational attainment, trip purpose, presence of covered sidewalks and walkways, and the presence of wide sidewalks and walkways are significant predictors of mode shift. Being a college graduate and shopping trips were associated to a decreased likelihood of mode shift. The presence of covered sidewalks and walkways increases the likelihood of mode shift to 3.14 times as compared to none while the presence of wide sidewalks and walkways increases the likelihood of mode shift to 3.15 times as compared to none. The results of this study can be used as a guide in determining which pedestrian facilities should be prioritized in CBDs as well as in future land developments.